Analysis of the Public Financial Investment in Elite Sport in Chile; [Análise Da Contribuição Financeira Para O Esporte de Elite No Chile]; [Análisis de la Contribución Financiera Al Deporte de Élite en Chile] - Cofre-Bolados, C (Universidade Federal do Rio Grande do Sul, 2023)
Funding is one of the most controversial areas when analyzing the likelihood of performance in elite sports. In order to establish the level of funding available in this area, it was necessary to establish certain conceptual margins with respect to elite sport and to determine the different sectors of sport that fit the proposed conceptual definition. Using a non-experimental descriptive method, based on empirical research in sports sciences and a meta-analysis strategy secondary information available on various websites of public services of Chile, together with yearbooks and information requested from entities linked to elite sport, Secondary information was collected that allowed knowing the different lines of funding from each of the factors and sub-factors of pillar 1 of the SPLISS model, proposed by De Bosscher et al. (2006) for the achievement of elite sport achievement that was part of the study. In conclusion, it can be established that a permanent increase in funding does not guarantee performance in elite sports. © 2023, Universidade Federal do Rio Grande do Sul. All rights reserved.